Molecular Breeding for Mitigation of Abiotic Stress in Projected Climate Change Scenario: Potentials and Limitat Developing and Underdeveloped Countries - Satya, P.; Maiti, R. K. (International Journal of Bio-resource and Stress Management, 2023)
If we look at the tasks to be accomplished by the farmers for survival of the mankind in the near future, a baffling situation arises. FAO projects that the global population is going to be over 9 billion by 2050, which needs at least 70% increase in crop productivity over the current scale (Alexandratos, 2006). Thus farmers have to produce almost 1½ of the current output. The projections for availability of cultivable land with good soil health and usable irrigation water are equally horrifying; both are decreasing steadily at an alarming rate. Several status reports have been published on effects of climate change on crop productivity and most of them project a shortfall of production in the future climatic conditions (Lobell et al., 2008; GOS, 2011)